Associations among Nosema spp. fungi, Varroa destructor mites, and chemical treatments in honey bees, Apis mellifera. Issue 4 (4th May 2022) - Little, Catherine M.; Shutler, Dave; Williams, Geoffrey R.
Abstract : Nosema spp. and Varroa destructor are common parasites of honey bee colonies. Beekeepers routinely treat colonies with the fungicide fumagillin to control Nosema and an array of miticides to control V. destructor . Interactions between these parasites and chemical treatments are poorly understood. We allocated honey bee colonies to distinct chemical treatment regimes and monitored parasite intensities in the subsequent year. Infections of Nosema and infestations of V. destructor were positively correlated. Fumagillin was effective at mitigating Nosema intensities only over the short term, suggesting that biannual application is essential. V. destructor intensities were higher in colonies that had been previously treated with miticides, reasons for this warrant further investigation.